GC-MS ANALYSIS OF SECONDARY METABOLITES OF SENGGANI LEAVES (Melastoma malabatrichum L.) - Nasution, Muhammad Yusuf; Rangkuti, Marlinda Nilan Sari; Situmorang, Nurbaity (JURNAL BIOSAINS, 2024)
Traditional medicinal plants have long been used and trusted by the community to treat various diseases. The senggani plant is useful for reducing fever (antispiretic), pain reliever (analgesic), urine laxative (diuretic), treating vaginal discharge (leukorrhea), and as a medicine for various types of wounds. This research was conducted using extracts of Melastoma malabatricum (L.) leaves extracted using methanol as a solvent. GC-MS analysis of secondary metabolites of senggani leaves (Melastoma malabatrichum L.) was carried out as a first step to determine the content of active secondary metabolite compounds contained in senggani leaves.The results of this study show that 8 peaks were observed during maximum run time of 40 min. The results revealed that, compounds such as 3-Hexadecyloxycarbonyl-5-(2-hydroxyethyl)-4-methylimidazolium, Melezitose, Thiosulfuric acid, Neophytadiene, 9-Icosyne, Phytol, Hexadecanoic acid dan 9-Octadecenoic acid (Z) were present in the methanolic extract of Melastoma malabatrichum (L.) which can mostly contribute to several therapeutic activities such as antimicrobial.